2020
DOI: 10.1007/s10984-020-09338-7
|View full text |Cite
|
Sign up to set email alerts
|

Designable elements of integrative learning environments at the boundary of school and work: a multiple case study

Abstract: Learning environment designs at the boundary of school and work can be characterised as integrative because they integrate features from the contexts of school and work. Many different manifestations of such integrative learning environments are found in current vocational education, both in senior secondary education and higher professional education. However, limited research has focused on how to design these learning environments and not much is known about their designable elements (i.e. the epistemic, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…We acknowledge that vocational education could take place both in school and at work sites (e.g. Bouw, Zitter, and De Bruijn 2020), and it is essential to study pedagogic practices in relation to learning at the boundary of school and work. However, current literature review is not aimed at clarifying this relationship.…”
Section: Understanding Pedagogic Practices To Support Vocational Learning At Workplacesmentioning
confidence: 99%
“…We acknowledge that vocational education could take place both in school and at work sites (e.g. Bouw, Zitter, and De Bruijn 2020), and it is essential to study pedagogic practices in relation to learning at the boundary of school and work. However, current literature review is not aimed at clarifying this relationship.…”
Section: Understanding Pedagogic Practices To Support Vocational Learning At Workplacesmentioning
confidence: 99%
“…Design choices are viewed to be highly context-dependent (Carvalho and Goodyear, 2018;Bouw et al, 2021;Heeneman et al, 2021), and indeed a wide range of design choices was found across the nine programs showing a wide range of manifestations of PA in practice. Higher education institutes seem to use the principles of PA to make design choices that fit their particular students, views on learning, and workplace characteristics and developments.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Since intentional design choices can thus determine to a large extent whether learning processes are stimulated (van den Akker, 2004;Carvalho and Goodyear, 2018;Bouw et al, 2021) and whether robust decision making is possible, PA is often described as a design issue (Torre et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The spider web is useful to design learning environments in a single context, such as a classroom in a school context, but seems less suitable to deal with typical design issues of vocational education, concerning both contexts of school and work. Indeed, the curricular spider web does not focus on specific designable elements that may support the school-work connectivity, namely, the epistemic, spatial, instrumental, temporal, and social elements that shape the activities that emerge at the school-work boundary in vocational education (Bouw et al, 2020;Markauskaite & Goodyear, 2017;Zitter & Hoeve, 2012).…”
Section: Curriculum Development In Vocational Educationmentioning
confidence: 99%